The Effect of Learning Tenses Using Abbreviated Formulas on Students’ Grammar Mastery at the Takhasus grade of Mazro’atul Lughoh Islamic Boarding School Pare Kediri - Yanti Ramiasih; Asrorul Mufidah (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2022)
The aim of this study is to investigate the effect of learning tenses using abbreviated formulas on students’ grammar mastery at the Takhasus grade of Mazro’atul Lughoh Islamic Boarding School Pare Kediri. The method of this study is quantitative by taking 20 students of the population, and using saturated sampling. This study was pre experimental research design conducted with one group. Before giving treatment, the writer gave pre-test. After four meetings, the writer gave the post-test. The scores of pre-test and post-test were collected from twenty essay questions, then, it was analyzed by using t-test. The findings of this study shows that learning tenses using abbreviated formulas on students’ grammar mastery was effective. It is proved by the result of the calculation of paired sample t-test with the sig (2 tailed) with the result was .000, and it was < 0.05. It is considered that the null hypothesis (Ho) in this study is rejected and the alternative hypothesis (Ha) is accepted, which states that there is a significant difference between students learning tenses before and after using abbreviated formulas. It means that learning tenses using abbreviated formulas affects students’ grammar mastery. Keywords : Grammar Mastery, Abbreviated Formulas, Tenses.